2022
DOI: 10.1093/pnasnexus/pgab003
|View full text |Cite
|
Sign up to set email alerts
|

LONGL-Net: temporal correlation structure guided deep learning model to predict longitudinal age-related macular degeneration severity

Abstract: Age-related macular degeneration (AMD) is the principal cause of blindness in developed countries, and its prevalence will increase to 288 million people in 2040. Therefore, automated grading and prediction methods can be highly beneficial for recognizing susceptible subjects to late-AMD and enabling clinicians to start preventive actions for them. Clinically, AMD severity is quantified by Color Fundus Photographs (CFP) of the retina, and many machine-learning-based methods are proposed for grading AMD severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…that learned from temporal, longitudinal changes in CFPs; this model achieved an accuracy of 0.762 (95% CI 0.733-0.792) in simultaneously grading disease severity at the current time point and in predicting progression to late AMD at a future time point. 45 Lastly, Liefers et al…”
Section: Ganjdanesh Et Al Developed a Generative Adversarial Network ...mentioning
confidence: 99%
See 1 more Smart Citation
“…that learned from temporal, longitudinal changes in CFPs; this model achieved an accuracy of 0.762 (95% CI 0.733-0.792) in simultaneously grading disease severity at the current time point and in predicting progression to late AMD at a future time point. 45 Lastly, Liefers et al…”
Section: Ganjdanesh Et Al Developed a Generative Adversarial Network ...mentioning
confidence: 99%
“…A number of studies used CFPs from the Age-Related Eye Disease Study (AREDS) clinical trial to train their neural networks. [41][42][43][44][45] Bhujyan et al applied a two-step approach: (1) classification of images according to disease severity using DL and (2) prediction of progression to advanced AMD using classical ML. 43 The hybrid model achieved 84% accuracy in predicting advanced AMD development (GA and nAMD) within 2 years.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…In addition to extensive research on the diagnosis and classification of AMD, AI has been used to predict the severity, disease progression, and therapeutic effect in patients with age-related macular degeneration. Ganjdanesh et al (2022) created a new DL model (LONGL-Net) based on ResNet-18 to predict the severity and progression of patients with age-related macular degeneration. They collected approximately 30,000 color fundus photographs for training and verifying the model.…”
Section: Application Of Artificial Intelligence In Retinal Vascular D...mentioning
confidence: 99%
“…Recent advancements have led to the consideration of longitudinal data components as distinct modalities for multimodal representation learning [17,18]. Research has shown that fusion strategies-combining features from multiple modalities into a joint representation-on longitudinal data components can improve various tasks such as sample generation [19], classification or prediction [20][21][22] and risk analysis [23].…”
Section: Joint Representation Learning For Longitudinal Datamentioning
confidence: 99%